Forensic Accounting and Fraud Detection in Nepali Banks - Neupane, Mukti Prasad; Sapkota, Chet Narayan (Madhyabindu Journal, 2026)
This paper overviews the role of forensic accounting in the detection of fraud in Nepalese banking sector. This study employs a descriptive and causal comparative research design and a questionnaire survey was carried out with 385 bankers from commercial and development banks in Chitwan. The collected data were analyzed using SPSS. Frequency Pearson correlation and multiple regression analysis statistical tools were employed. Similarly, the forensic accounting tools like whistleblower hotlines, ethical philosophy, review of digital fraud and sustainable governance systems, as indicated in the findings, have a very strong positive correlation and hence they are the most crucial factors influencing the effectiveness of forensic accounting in fraud detection. Nevertheless, the degree of fraud detection is only weakly correlated or even negatively correlated with the use of control systems and litigation hotlines as seen in the figure. The study suggests that to effectively deal with the recent financial frauds, ethical leadership, forensic tools, and internal controls must be enhanced. Besides this, increasing the protection of whistleblowers and improving the efficiency of litigation hotlines are also the measures that can help to further prevent fraud in Nepali banks.